Interaction of Laser Radiation with Solids -Review Articles - El-Adawi, M.K; Shalaby, S.A; ABDEL-Ghany, S.E.S (International Journal of Natural Sciences Research, 2015)
A historical highlight to Laser acronym is given .Moreover, Laser heating effects induced in solid targets for one phase and multiphase cases are provided. Metallic and nonmetallic materials are highlighted. The effect of the temperature dependence of the front surface of the irradiated targets on the thermal response are considered. A bibliography of some fundamental papers published on the subject up to 2014 is presented.